2017
DOI: 10.1038/s41598-017-09902-x
|View full text |Cite
|
Sign up to set email alerts
|

Photobleaching in STED nanoscopy and its dependence on the photon flux applied for reversible silencing of the fluorophore

Abstract: In STED (stimulated emission depletion) nanoscopy, the resolution and signal are limited by the fluorophore de-excitation efficiency and photobleaching. Here, we investigated their dependence on the pulse duration and power of the applied STED light for the popular 750 nm wavelength. In experiments with red- and orange-emitting dyes, the pulse duration was varied from the sub-picosecond range up to continuous-wave conditions, with average powers up to 200 mW at 80 MHz repetition rate, i.e. peak powers up to 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 35 publications
2
69
0
2
Order By: Relevance
“…And it was found that the depth dependence of resolution was consistent with the depth dependence of depletion efficiency (Takasaki et al, 2013). Then the configuration of the vortex phase plate (VPP) was improved to transmissible liquid crystal devices (tLCD) which enabled the modification of optical properties over a wide wavelength region, at least 450-900 nm, at a high conversion efficiency (Ipponjima et al, 2014;Otomo et al, 2015a). Thus, this helped TPE-STED technique to ameliorate photobleaching and phototoxicity to go further.…”
Section: Two-photon Excitationmentioning
confidence: 85%
See 1 more Smart Citation
“…And it was found that the depth dependence of resolution was consistent with the depth dependence of depletion efficiency (Takasaki et al, 2013). Then the configuration of the vortex phase plate (VPP) was improved to transmissible liquid crystal devices (tLCD) which enabled the modification of optical properties over a wide wavelength region, at least 450-900 nm, at a high conversion efficiency (Ipponjima et al, 2014;Otomo et al, 2015a). Thus, this helped TPE-STED technique to ameliorate photobleaching and phototoxicity to go further.…”
Section: Two-photon Excitationmentioning
confidence: 85%
“…In essence, pulsed STED had the advantage of relatively low average power, in which condition fluorophores were not prone to be bleached. The dependence of photobleaching on the pulse duration and the STED power was investigated recently (Dyba & Hell, 2003;Castello et al, 2016;Oracz et al, 2017). The results are of significant guide to further knowledge of pulsed STED in study of reducing bleaching.…”
Section: Time-gatingmentioning
confidence: 99%
“…Concretely, recent adaptive scanning strategies [66][67][68] have proven key to reducing the overall light dose applied to the sample. These conceptual additions to STED/RESOLFT imaging reduce photobleaching [69] and are advantageous for live-cell imaging. Thus, they have allowed the resolution of STED microscopy to be pushed even closer to the <20 nm regime for organic fluorophores and for routine users, under realistic cell-imaging conditions.…”
Section: Recent Developments: Nanoscopy At the Minimummentioning
confidence: 99%
“…11 More recently it has been shown that STED microscopy based on sub-nanosecond (∼ 600-1000 ps) pulsed lasers substantially reduces the photo-bleaching compared to early pSTED implementations: 12 photo-bleaching is supra-linear with the STED beam intensity. 13,14 In this case, since the pulse-width is comparable with the excited-state lifetime τ f l and the peak intensity reduces (for a given average intensity of the pulse), the fluorescence emitted during the action of the STED beam is not anymore negligible and the benefit of time-gating is relevant. For these reasons, most of the current pSTED microscopy implementations -including the commercial systems -relies on sub-nanosecond fiber laser and implement a time-gated detection (gated-pSTED microscopy).…”
Section: Introductionmentioning
confidence: 99%